TAFSIR AYAT RAHMATAN LIL ‘ALAMIN MENURUT PENAFSIR AHLU SUNNAH, MUKTAZILAH, SYIAH, DAN WAHABI - Lukman Lukman (Millah: Journal of Religious Studies, 2016)
This study aims to determine whether the source of conflict in the body of the Mus-lims also caused differences in the interpretation of paragraph rahmatan lil ‘Alamin in Surat al-Anbiya’ verse 107. This limits the research object of research only on four major currents of thought in Islam, namely Ahlu Sunnah, Mu’tazilite, Shia and Wahabi. According to the flow Ahlu Sunnah that are faithful to God, the grace bestowed in this world and hereafter. For those who do not believe in Allah SWT, then the form of grace is not disegerakannya catastrophe in the world as the peoples before Islam. Then interpretation  Mu’tazilite flow, explicitly the existence of a disadvantage for non-believers. That the Prophet Muhammad brought happiness to those who followed him and who did not follow it, then it comes out of his lust which constrict parts of grace. Furthermore, the flow Shiite explicitly showing reluctance for people who do not believe in the grace. That Allah showed unbelievers to believe and give him the signs, but the unbelievers not find it. Lastly, the interpretation of Wahabism that explicitly rampart against the unbelievers. That mercy for the infidels against Islam is to be speeded up his death and it is better for them. Because with no faith and hostility they will just tuck torment in the hereafter.